2016
DOI: 10.3390/ijms17101707
|View full text |Cite
|
Sign up to set email alerts
|

Age- and Brain Region-Specific Changes of Glucose Metabolic Disorder, Learning, and Memory Dysfunction in Early Alzheimer’s Disease Assessed in APP/PS1 Transgenic Mice Using 18F-FDG-PET

Abstract: Alzheimer’s disease (AD) is a leading cause of dementia worldwide, associated with cognitive deficits and brain glucose metabolic alteration. However, the associations of glucose metabolic changes with cognitive dysfunction are less detailed. Here, we examined the brains of APP/presenilin 1 (PS1) transgenic (Tg) mice aged 2, 3.5, 5 and 8 months using 18F-labed fluorodeoxyglucose (18F-FDG) microPET to assess age- and brain region-specific changes of glucose metabolism. FDG uptake was calculated as a relative st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
51
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 40 publications
3
51
0
Order By: Relevance
“…Our earlier studies reported that those mice exhibited notable learning and memory deficits at 8 months of age (Li X.-F. et al, 2016). In this study, we further showed that PBS-treated AD mice exhibited notable disorders in the anxiety and recognition compared with WT mice.…”
Section: Discussionmentioning
confidence: 94%
“…Our earlier studies reported that those mice exhibited notable learning and memory deficits at 8 months of age (Li X.-F. et al, 2016). In this study, we further showed that PBS-treated AD mice exhibited notable disorders in the anxiety and recognition compared with WT mice.…”
Section: Discussionmentioning
confidence: 94%
“…The APP/PS1 transgenic mouse is the most commonly used AD model, which develops spatial memory impairment, increased Aβ deposition in the brain, synaptic loss, and neuronal loss similar to those features observed in AD [39,40]. It has been reported that the amyloid plaque can occur in the neocortex at 6-8 weeks and signi cantly increase at 8 months old [41], the synaptic dysfunction appears at about 3 months old [42], and the cognitive disability starts to show at about 6 months old in the APP/PS1 mice [43].…”
Section: Discussionmentioning
confidence: 99%
“…The transgenes were confirmed by PCR genotyping of mouse tail tissue [31,32]. Only female mice were utilized because female APP/PS1 mice develop cognitive deficits faster than the male mice [33].…”
Section: Animalmentioning
confidence: 99%
“…Previous study used 18F-labeled fluorodeoxyglucose (FDG) microPET detecting the brains of APP/PS1 transgenic (TG) mice to evaluate age-and brain region-specific changes of glucose metabolism, which demonstrated that APP/PS1 mice showed intact cognition at age 2 months (m), learning deficits at 3.5 m, learning and memory deficits at 5 m, and further learning and memory impairments at 8 m [33]. It seems that APP/PS1 mice of 2 m mimic the preclinical stage of AD (prodromal-AD), whereas APP/PS1 mice of 3.5 m, 5 m, and 8 m exhibit subclinical, early clinical, and midclinical signs of AD (symptomatic-AD) [33]. As medium-/longterm exercise induces promising improvements in learning and memory [9,34], we studied the impact of medium-/long-term treadmill exercise (for 12 and 24 weeks, respectively) on mice at different stages of AD.…”
Section: Animalmentioning
confidence: 99%